Demystifying Discussion Section in Engineering Laboratory Reports - Veeramuthu Veerappan, Mokhtarrudin Ahmad, Wei Hui Suan, Afizal Md Aris (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This study examines the genre of Engineering Laboratory Reports (ELR) discussion section written by Electrical Engineering Undergraduates in a higher learning institution. The aims of this study are to identify the rhetorical moves and combinations of move patterns used by engineering students to write discussion section of ELR. A genre analysis is deemed important to identify writing patterns and convention practices of engineering undergraduate students thus a corpus of N= 35 was selected from electrical engineering students in their third and fourth year of study. This study adopted an interdisciplinary approach to address the analytical framework based on Genre Theory and Ngowu [1] analytical model was used for data analysis. The procedures of the move analysis were based on Biber [2] BCU Approach. A pilot test was conducted to determine the model that fits the best to describe moves and steps of ELR. The study benchmarks a move or step to be present in at least 60% of the reports. The results show Presenting Experimental Outcomes as the main move followed by Step 1 Restating purpose or procedures of experiment as an optional step while Step 2 Stating Specific outcome and Step 3 Interpreting outcomes as mandatory steps. The two steps in discussion section (step 2 and 3) are in cyclical pattern and most frequently occurred along with move 4. Step 3 is extensively written by employing various thinking skills that are explicitly written without much manipulation and speculation to the information. As discipline-specific writing continues to gain importance in EAP context, this study determines ways to help students to acquire discipline-specific literacy and to shed light on discoursal research methodology.